LEGIUN MANGKUNEGARAN TAHUN 1916 – 1942 DAN IMPLEMENTASINYA DALAM PEMBELAJARAN SEJARAH - Pratiwi, Anita Dhian (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2014)
The purpose of this research is to find out: (1) the history of Legiun Mangkunegaran, (2) changes and dinamics Legiun Mangkunegaran in 1916 ? 1942, (3) the impact of Legiun Mangkunegaran for the stability of safety of Surakarta at 1916 ? 1942, (4) the implementation of Legiun Mangkunegaran at 1916 ? 1942 in learning history to the students of eleventh grade of senior high school.The research method that is uses is historical method. The source of data that is used in this study is primary and secondary sources. Historical method was the critical process of examining and analyzing the past recording and heritage, and then reconstructing them based on the data obtained so that a historiography results. The procedure of historical method included heuristic, critical, interpretation, and historiography.Based on the result of the research can be concluded that: (1) Legiun Mangkunegaran was formed at July 29, 1808 based on decree of Governor Lieutnant General Daendels, Legiun Mangkunegaran was formed based on two interests they are as reserve that is used by the dutch east Indian army and as a political tool that is used to scare-discouraging any attempt to abolish political glassware, (2) in accordance with the change of politic at 20th century, Legiun Mangkunegaran change in the terms of both quality and quantity, (3) the exiatence of Legiun Mangkunegaran makes Mangkunegaran especially and Surakarta generally having a good stability of security, (4) Legiun Mangkunegaran in 1916 -1942 can be implemented in curriculum 2013 as learning material of history to the eleventh grade of senior high school. Kata Kunci: Legiun Mangkunegaran, Military, Learning the History